Features of Inclusion Parents and Children with Autism Disorders in Productive Cooperative Activities - Shcherbakova A. M., Vasil'kova E. A. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2021)
The article reveals the problem of including a parent and a child with autism spectrum disorder in cooperative activities using the example of two families participating in the research. The theoretical foundations of this problem and the practical results obtained at the first stage of the study by questioning parents, and also by observing the cooperative productive activities of the child and the parent during the drawing lessons. The question of the importance of parental involvement in the child's rehabilitation process is considered.
Keywords: психолого-педагогическое сопровождение; расстройство аутистического спектра; продуктивная деятельность; psychological and pedagogical support; Autism Spectrum Disorder; совместная деятельность родителя и ребенка; реабилитационный процесс; Сooperative activity of parent and child; productive activity; rehabilitation process